How Much Pigment Should Flowers Have? Flowers With Moderate Pigmentation Have Highest Color Contrast - van der Kooi, Casper J. (Frontiers in Ecology and Evolution, 2021)
Floral pigments are a core component of flower colours, but how much pigment a flower should have to yield a strong visual signal to pollinators is unknown. Using an optical model and taking white, blue, yellow and red flowers as case studies, I investigate how the amount of pigment determines a flower’s colour contrast. Modelled reflectance spectra are interpreted using established insect colour vision models. Contrast as a function of the amount of pigment shows a pattern of diminishing return. Low pigment amounts yield pale colours, intermediate amounts yield high contrast, and extreme amounts of pigment do not further increase, and sometimes even decrease, a flower’s colour contrast. An intermediate amount of floral pigment thus yields the highest visibility, a finding that is corroborated by previous behavioural experiments on bees. The implications for studies on plant-pollinator signalling, intraspecific flower colour variation and the costs of flower colour are discussed.